Blood Pressure Response During Resistance Training of Different Work-to-Rest Ratio. Issue 2 (February 2019) - Paulo, Anderson Caetano; Tricoli, Valmor; Queiroz, Andréia C.C.; Laurentino, Gilberto; Forjaz, Cláudia L.M.
Abstract : Abstract: Paulo, AC, Tricoli, V, Queiroz, ACC, Laurentino, G, and Forjaz, CLM. Blood pressure response during resistance training of different work-to-rest ratio. J Strength Cond Res 33(2): 399–407, 2019—Changes in the work-to-rest ratio (W:R) of resistance training protocols (RTPs) (i.e., decreasing work or increasing rest) reduce the marked elevation in blood pressure (BP) that occurs during RTP execution. However, whether changes in RTP structure without changing W:R can change BP responses to RTP is unknown. To investigate the effect of different structures of rest intervals and number of repetitions per set on BP response among RTP equated and nonequated for W:R, 20 normotensive participants (25 ± 4 years) performed 4 different RTP of the leg extension exercise with the same work but different W:R structures. Two protocols followed the recommendations for cardiovascular disorders: (a) HIGHW:R -3×15:44s–3×15:44s (set×reps:rest between sets), which has high W:R (45reps:88s) and (b) LOWW:R -3×15:88s–3×15:88s, which has low W:R (45reps:176s). The other 2 protocols were W:R-equated to LOWW:R (45reps:176s): (c) LOWW:R -9×5:22s and (d) LOWW:R -45×1:4s. Systolic BP (ΔSBP) and diastolic BP (ΔDBP) were assessed by finger photoplethysmography. There were significant main effects for ΔSBP after RTP ( p ⩽ 0.05): HIGHW:R -3×15:44s = LOWW:R -3×15:88s > LOWW:R -45×1:4s > LOWW:R -9×5:22s (+87 ± 5 and +84 ± 5 vs. +61 ± 4 vs. 57 ± 4 mm Hg). For ΔDBP, there was a significant interaction between RTP and moment ( p ⩽ 0.05). Thus, HIGHW:R -3×15:44 > LOWW:R -3×15:88s > LOWW:R -45×1:4s > LOWW:R -9×5:22s (+53 ± 5 vs. +49 ± 5 vs. +44 ± 4 vs. +38 ± 3 mm Hg). HIGHW:R -3×15:44s produced the highest increase in ΔDBP, and LOWW:R -9×5:22s produced the lowest increase in ΔSBP and ΔDBP. Our findings may help the development of RTP protocols that may mitigate pressure peaks without changing important exercise variables (i.e., volume or duration).